Sintesis Biodiesel Dari Minyak Nyamplung (Calophyllum Inophyllum) Menggunakan Katalis Geopolimer: Pengaruh Konsentrasi Katalis Dan Rasio Mol Minyak:Metanol - Sugesti, Heni; Saputra, Edy; Helwani, Zuchra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Biodiesel is a product of transesterification reaction fat/oil and methanol with the aid of catalyst. Catalysts is commonly used in the production of biodiesel is strong base catalysts such as NaOH and KOH which is difficult to separate from the product of the reaction because it has the same phase as the reactant. Therefore, it is necessary to develop catalyst technology in order to get the production process becomes more economical, applicable and environmentally friendly, one of the catalyst is geopolymer. Geopolymers are synthesized by reacting potassium silicate, metakaolin, and bottom ash. Geopolymers is used in transesterification reaction. The process variables are weight of oil 50 grams, stirring rate 400 rpm, reaction time 120 minutes, and temperature of 65 oC, with catalyst 2% (w/w) and mole ratio of methanol:oil 1:12. The yield of biodiesel 96.62% with density 878.3 kg/m3, viscosity 4.395 mm2/s, the acid number of 0.3575 mg-KOH/g biodiesel and the flash point 134.25 °C comply with the SNI standards (SNI 7182: 2015).Keywords: biodiesel, calophyllum inophyllum oil, geopolymer, transesterification, yield